Multiculturalism: concepts in the social sciences - Watson, C W. (New Delhi, 2002)
Multicultural and multiculturalism are words frequently used to describe the ethnic diversity that exists everywhere in the world today. However, there is some confusion about what precisely they signify. Do they simply describe diversity or are they advocating a particular response to that diversity? This book looks at some of the debates associated with these words and with the concepts attached to them. In particular the arguments for and against multiculturalism are examined in the context of modern states in different political and historical circumstances. Attitudes and emphases in relation to multiculturalism differ, it is argued, from one country to another and the chapters of the book draw out the dimensions of difference. with examples ranging from Europe and the USA to South East Asia and China. The focus of the discussion is placed on issues such as minority rights, education, religious tolerance and the trend to global homogenization. The result is a concise and balanced overview of a topic within wide appeal across undergraduate and postgraduate courses from sociology and politics to cultural studies and anthropology.
Keywords: Culture